Hormonal regulatory networks in spinal cord injury: mechanistic insights, crosstalk, and therapeutic innovations - Guo, Wenliang; Wu, Yinteng; Zhao, Shijian; Xu, Jianwen (Frontiers in Endocrinology, 2025)
Spinal cord injury (SCI), a debilitating neurological disorder with complex pathophysiology, involves primary mechanical trauma followed by multifactorial cascades of secondary inflammation, oxidative stress, and apoptosis. Hormones have emerged as a research focus in SCI therapeutics due to their neuroprotective properties. As pivotal regulators of cellular signaling, hormones exhibit dual roles in either exacerbating or mitigating secondary damage. This review synthesizes three decades of research, highlighting that hormones such as corticosteroids, melatonin, and estrogen demonstrate significant therapeutic potential in animal models and clinical studies, though controversies persist regarding their efficacy and safety profiles. Key findings include: (1) Glucocorticoids, exemplified by methylprednisolone (MP), suppress inflammation and reduce tissue damage but face skepticism over long-term benefits, with high-dose regimens correlating with significant adverse effects such as gastrointestinal bleeding, hyperglycemia, and metabolic complications; (2) Melatonin exerts multi-target neuroprotection by modulating autophagy, inhibiting apoptosis, and suppressing inflammasome activation; (3) Sex hormones (e.g., testosterone, progesterone) improve functional recovery through metabolic balance regulation and neural regeneration, while estrogen enhances angiogenesis and motor function via the synergistic involvement of multiple receptor-mediated genomic (ERα/ERβ) and non-genomic (GPER) signaling pathways. The non-genomic actions rapidly activate kinase cascades, such as PI3K/Akt-CREB and ERK, which in turn regulate both immediate cellular functions and gene expression profiles, contributing to the overall neuroprotective effects; (4) Combinatorial therapies (e.g., MP with neurotrophic factors) and novel delivery systems (e.g., nanoparticle-based drug carriers) represent promising strategies to optimize therapeutic outcomes. These advances elucidate the multidimensional mechanisms of hormonal interventions while revealing critical challenges, including dose-dependent adverse effects, antagonistic effects in polypharmacy, and unresolved long-term safety concerns. Overall, hormonal therapies for SCI present a “dual-edged sword” of efficacy versus risks, necessitating future innovations in precision regulation and mechanistic exploration to bridge translational gaps.